2010
DOI: 10.5152/jtgga.2010.34
|View full text |Cite
|
Sign up to set email alerts
|

Association between the extent of DNA damage in the spermatozoa, fertilization and developmental competence in preimplantation stage embryos

Abstract: Objective: To examine the fertilizing ability and DNA damage response of preimplantation stage embryos derived from the γ-irradiated mouse sperm carrying varying amounts of DNA strand-breaks. Material and Methods:The DNA damage in the sperm was induced by exposing the testicular area to different doses of γ-radiation. After mating with healthy female mice, sperm zona binding, fertilizing ability of DNA damaged sperm and developmental competence of embryos derived from the DNA damaged sperm were assessed. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Besides, damage to the DNA does not always affect motility and fertility, as seen in brown-marbled grouper, Epinephelus fuscoguttatus (Yusoff et al, 2018). Upadhya et al (2010) found that the affected sperm with good motility possess the capacity to fertilize an egg, followed by the development of potentially damaged genomes, and, consequently, causing larvae abnormality. Horvath & Urbanyi (2001) recorded higher amounts of abnormal larvae in eggs fertilized using cryopreserved sperm, of which some were haploid (Miskolczi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, damage to the DNA does not always affect motility and fertility, as seen in brown-marbled grouper, Epinephelus fuscoguttatus (Yusoff et al, 2018). Upadhya et al (2010) found that the affected sperm with good motility possess the capacity to fertilize an egg, followed by the development of potentially damaged genomes, and, consequently, causing larvae abnormality. Horvath & Urbanyi (2001) recorded higher amounts of abnormal larvae in eggs fertilized using cryopreserved sperm, of which some were haploid (Miskolczi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm DNA integrity is essential for accurate transmission of genetic material to the offspring (3). It has been shown that paternal DNA damage can lead to pre-implantation developmental delay and compromised post-implantation developmental potential in mice (4)(5)(6). Hence sperm preparation method for assisted reproduction techniques should aim at minimizing the potential risk caused by abnormal sperm on the outcome.…”
Section: Introductionmentioning
confidence: 99%